Ice Camp Oceanographic Be-7 Measurements. Version 1.0 ... - Kadko, D.; Rosentiel School Of Marine And Atmospheric Science RSMAS, University Of Miami (UCAR/NCAR - Earth Observing Laboratory, 2007)
This dataset contains Be-7 concentrations for stations occupied during October 1997 and June through October 1998. For each sample, approximately 700 L of seawater from the upper 50m of the water column was pumped through an iron-impregnated acrylic fiber. On land, the fibers were dried, ashed, and placed in a Marenelli beaker for gamma counting. To estimate the atmospheric deposition of Be-7, samples of snow were also collected and plastic buckets were deployed to collect fallout over known time periods. ...